Public Therapeutic Communication Analysis on Kanker_Fighter’s Instagram Account - Rulinawaty; Achmad Daengs GS; Sulistyo Andarmoyo; Sara Surya; Rachmat Susanto (Jurnal Komunikasi Profesional, 2022)
Cancer disease is a devastating disease that could change someone’s life and relationship drastically. Cancer have been seen as a disease that revolves around strong donation interest. By donating to certain organization or community, the cancer patient could get a help from them. Using social media is their strong method to communicate their purpose and agenda to reach the donation candidate or those who can help and expand the attention of cancer disease. In Indonesia, disease is strongly influenced by religious and mystical figure and myths, thus, their method still crossing each other with actual medical workers, it is why Kanker_Fighter account still also has some PR blunder in their Instagram account. These phenomenon serves as Therapeutic Communication interference for actual medical worker in the field. With the strong donation biased method, lack of research, and Therapeutic Communication interference, it could stagnate the cure for cancer patients.